Modeling of FinTech market development (on the example of Ukraine) - Alina Bukhtiarova; Arsen Hayriyan; Nikol Bort; Andrii Semenog (Innovative Marketing)
FinTech startups and services are one of the most dynamic segments of the modern economy. New financial technologies have already attracted many investors and form millions of budgets. Changing the traditional financial services concept, FinTech companies formed a new niche within the financial services market, the dynamic development of which determines the relevance of the development and implementation of an effective regulatory and oversight system.The purpose of the article is to develop an economic and mathematical model for forecasting the development of the FinTech market on the example of Ukraine. In order to study the development of the FinTech industry, a multiple regression model was presented. The model describes the dependence of the total investment value of FinTech from venture investments in financial technology, venture investments in other technologies and venture investments in online lending. Based on this model, the effect of attracting investments with new FinTech projects on the total volume of investments in the industry was clarified. According to the model, with a change in investments in FinTech by 1%, the total rate of venture investments decreases by 0.03, funds in new projects of other companies grow by 0.05, and venture investments in online lending increase by 0.89. According to the analysis of regulatory legislation in the foreign countries of the FinTech services sphere, it was found that the regulation of most of the risks associated with the development of FinTech services falls within the competence of different supervisory authorities, requiring cross-sectoral cooperation between public institutions.